(3QhVI GdefGXQ aj Yde GdChGFd hGdChGNQs - (3GHf GdTMfI GdUZjQ , eMeO Hf eMeO Hf eMeO Hf eMehO Hf ZGRj GdKbaj GdMdHj, CHh GdaVd Hf CHj GdhdjO,J (B890 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMSf cd TF Ndbg s
(3BNQgG (B:s
(3hMSHfG Gddg hfYe Gdhcjd hbO GfJgi ai GdeUQGY GdKGfi Edi SfI (B806 s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B92s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B147 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs